2018
DOI: 10.36597/jellt.v2i2.3269
|View full text |Cite
|
Sign up to set email alerts
|

Improving Students’ Speaking Skill Through You Tube Video Project for Nursing Department

Abstract: This study aims at discovering the effect of You Tube video project to improve students' achievement in speaking skill including pronunciation, grammatical accuracy, vocabulary, fluency, and interactive communication. It used an experimental design involving 83 Nursing students in Bantul: 44 students of Control group and 39 students of Experimental Group using simple random sampling technique. This study used statistical t-test to discover the effect of using You Tube video project in improving the students' s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…(2019, p. 101) showed that “the students' speaking skill was improving in three aspects 1) accuracy, 2) fluency, 3) performance”. Similar findings on the effectiveness of YouTube videos in improving students’ speaking skills were reported by different scholars (see Albahlal, 2019 ; Arroyyani, 2018 ; Pratama et al., 2020 ; Setiawan and Wiedarti, 2020 ; Tristiana and Swondo, 2020 ).…”
Section: Discussion Of Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…(2019, p. 101) showed that “the students' speaking skill was improving in three aspects 1) accuracy, 2) fluency, 3) performance”. Similar findings on the effectiveness of YouTube videos in improving students’ speaking skills were reported by different scholars (see Albahlal, 2019 ; Arroyyani, 2018 ; Pratama et al., 2020 ; Setiawan and Wiedarti, 2020 ; Tristiana and Swondo, 2020 ).…”
Section: Discussion Of Resultssupporting
confidence: 84%
“…Different scholars reported similar findings on the effectiveness of YouTube videos in improving students’ speaking skills (see Albahlal, 2019 ; Arroyyani, 2018 ; Pratama et al., 2020 ; Setiawan and Wiedarti, 2020 ; Tristiana and Swondo, 2020 ). Qomar (2016) examined the use of YouTube in enhancing students' speaking performance and found that YouTube could improve students' speaking skills.…”
Section: Review Of Related Literaturementioning
confidence: 74%
See 1 more Smart Citation
“…The results showed that there was an improvement in the students' fluency, vocabulary, pronunciation, grammar, and comprehension. Arroyani (2018) explored on improving Nursing department students' speaking skills through a YouTube video project. The result of the pre-test and post-test showed that the significance of the t-test was higher than the t-table.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, YouTube has a variety of videos containing learning materials as well as short stories that contribute to the development of writing ideas. So far, many studies have used YouTube as a source of learning to speak English (Lee & Liang, 2012;Arroyyani, 2018;Kartikasari, 2018;Prasetianing Jati, Saukah, & Suryati, 2019;Tristiana & Swondo, 2020;Sanoussi, Al Jawad, & History, 2020;Nuha & Saputri, 2021;Syafiq, Rahmawati, Anwari, & Oktaviana, 2021), but this research has made a different contribution, namely the development of writing skills. This finding also illustrates that feedback from the use of digital videobased learning resources is very good (Prilop, Weber, & Kleinknecht, 2020).…”
mentioning
confidence: 99%